Rolling work and power in high-speed finishing blocks of wire mills - V. V. Fillippov; A. A. Gorbanev; S. M. Zhuchkov; V. A. Tischenko; A. B. Steblov (Литьë и металлургия)
It is shown that with real drawing-down coefficients used in stand finishing blocks at hot rolling of steel wire rod the rolling speeds when metal can break in strand exit plane are impossible to reach in practice. At rolling of nonferrous wire rod in existing blocks of finishing stands it is necessary to take into account influence of dynamic effect in the deformation centre and to define maximum rolling speed securing solidness of metal at its exit from stands.